Serial Coupling of Ion‐Exchange and Size‐Exclusion Chromatography to Determine Aggregation Levels in mAbs in The Presence of a Proteinaceous Excipient, Recombinant Human Serum Albumin. Issue 2 (1st December 2014) - Weisbjerg, Paul Luigi Gargani; Caspersen, Mikael Bjerg; Cook, Ken; De Weert, Marco Van
<x xml:space="preserve">Abstract</x> Aggregation levels of therapeutic proteins may be difficult to determine in mixtures containing other proteinaceous excipients. We performed a feasibility study of using serial coupling of an anion exchange and size exclusion column to determine the aggregation levels of four different model monoclonal antibodies (mAb) mixed with the model proteinaceous excipient recombinant human serum albumin (rHSA). For three of the four mAbs suitable elution conditions could be established. From the limitations imposed by the pI of the rHSA, the pI of the mAb and the nature of the columns used, it was possible to propose a set of general conditions that allows quantification of the aggregation level of a therapeutic protein in the presence of a proteinaceous excipient: The excipient protein and protein of interest should differ in pI by a minimum of 0.5 units, and the pI of the protein of interest should not be higher than ca. 8.5. © 2014 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 104:548–556, 2015